ANALISIS STRATEGI PEMASARAN PADA PT. GERIN SURYA GEMILANG - Retnolia, Austina; Sitio, Arifin (Universitas Mercu Buana, 2017)
Increased business competition requires companies to always evaluate the marketing strategy undertaken. Every company will want to stay in business competition and increase profitability. The use of effective SWOT analysis can play an important role in determining competitive strategy, in order to know the strengths, weaknesses, opportunities and threats faced by the company in maintaining the viability and continuity of the company. The purpose of this study is to evaluate marketing strategies implemented by the company to improve the profitability of the company. This study uses primary data obtained through observation, interviews, and questionnaires and secondary data in the form of company reports. This research is done by using IFE analysis method to analyze internal factor, EFE analysis for external factor, then, incorporated into quantitative model that is IE Matrix, SWOT Matrix, SPACE and QSPM. The result of analysis shows that by using QSPM Matrix, then strategy chosen to support the achievement of the objectives of the company is Market Penetration Strategy.